Influence of cations on optical properties of iodobismuthates. (15th March 2020) - Pandey, Souvik; Chattopadhyay, Taraknath; Dev, Samrat; Patil, Yogesh; Carpenter-Warren, C.L.; Sinha, Chittaranjan
Graphical abstract: Abstract: Synthesis of iodobismuthates and tuning their properties attracted a lots of attention due to their contribution in developing opto-electronic devices. Two 1-D polymeric iodobismuthate compounds, [2, 6-(NH2 )2 PyH][BiI4 ]n (1 ), [4-NMe2 PyH][BiI4 ]n (2 ), [Py: Pyridine] have been reported, where structurally similar polymeric anionic iodobismuthate is stabilised by two different pyridinium cations namely 2, 6-bis(amino)pyridine and 4-( N, N -dimethylamino)pyridine derivatives. The compounds have been characterised by single crystal XRD, IR and elemental analysis. It is interesting to observe that the structurally similar compounds differ drastically in their optical properties because of slight variation in the cations. Comparison in structural features and their thermal, optical properties (band gap: 1.91 eV (1 ); 2.10 eV (2 )) have been discussed. Thermochromism is exhibited by 1 . DFT studies of compound 1 has been performed considering the crystal structure measured at two different temperature and the role of cation in tuning the optical properties of iodobismuthates has been established.